Language Pedagogy and Teacher Identity: A Decolonial Lens to English Language Teaching From a Teacher Educator’s Experience - Diego Ubaque-Casallas (Profile: Issues in Teachers' Professional Development)
This paper describes a narrative study that emerged from various conversations with an English language teacher at a public university in Bogotá, Colombia. This research is based on intersectional narratives to locate the intersections between English language pedagogy and the identities of English language teachers. Second, the study examined discourses that can construct English language pedagogy and teachers’ identities by avoiding simplistic generalizations and essentialisms. Findings suggest that although there are still colonial roots that repress other ways of being and doing, English language pedagogy goes beyond the instrumental sense of teaching. As such, English language pedagogy is about transformation as it is never static because it is an extension of identity.